Yeast-activated sludge model for aerobic degradation of a non-fermentable substrate. Issue 46 (1st October 2016) - Frigon, Matthew Dubois; Liu, Dongfang; Young, James
Abstract: This paper uses a combination of models and unique features not found in other models to develop a yeast-activated sludge model for modeling yeast kinetics while degrading an aerobic, non-fermentable substrate. Respirometry is used in conjunction with carbohydrate testing to determine model parameters and kinetics for yeast-activated sludge consuming glycerol at 30 g/l salinity. The data and model show that yeast metabolism begins with exponential growth similar to bacteria. After a minimum substrate level is reached, metabolism switches to storage/consumption of stored material. This phase is followed by a decay phase that is characterized by consumption of a portion of the material stored in the yeast cells. Values for kinetic parameters of the model are provided after fitting the model to four different substrate concentrations. Through the model, the differences between operation of bacterial and yeast systems become apparent and are explained.